1999
DOI: 10.1016/s1074-7613(00)80037-0
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for the Major Histocompatibility Complex Class II Transactivator CIITA in the Repression of IL-4 Production

Abstract: Class II transactivator (CIITA) is known as a coactivator for MHC class II gene expression in antigen-presenting cells. Surprisingly, when CIITA-/- CD4 T cells were stimulated in the presence of IL-12, they produced not only IFNgamma but also high levels of IL-4. The IL-4 production is due to the accumulation of IL-4 gene transcripts in Th1 cells. This transcriptional control is observed in T cells differentiating to the Th1 but not Th2 lineage, consistent with induction of expression of the CIITA gene in T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(128 citation statements)
references
References 67 publications
7
117
4
Order By: Relevance
“…This suggests that CIITA is highly dedicated to the regulation of MHC-II expression. Nevertheless, a series of reports have implicated CIITA in the regulation of a wide variety of other genes functioning within and outside the immune system [8][9][10][11][12][13][14]20]. These reports suggested that CIITA might play a pleiotropic role in various biological processes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that CIITA is highly dedicated to the regulation of MHC-II expression. Nevertheless, a series of reports have implicated CIITA in the regulation of a wide variety of other genes functioning within and outside the immune system [8][9][10][11][12][13][14]20]. These reports suggested that CIITA might play a pleiotropic role in various biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have established that deregulated CIITA expression has an impact on cytokine gene activation during Th1/Th2 differentiation [8,15,16,18]. Th1 cells from CIITA-deficient mice were found to exhibit de-repressed IL-4 expression [8,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations